2021
DOI: 10.1055/s-0041-1730086
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Spectrum of Movement Disorders in Neurology Inpatients in a Tertiary Care Centre

Abstract: Background Little data are available on the spectrum of movement disorders in inpatients, particularly those admitted in neurology specialty. This may be related to the fact that patients presenting with movement disorders are usually evaluated from outpatient clinics. Objective The aim of this study is to provide data on the pattern of movement disorders in neurology inpatients. Materials and Methods Patients admitted through emergency department or neurology clinic with complaints of movement abnormalities w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Movement disorders were the presenting feature in seven (14%) children. Two studies noted that SSPE contributed to movement disorders among 5.7% of 53 adults and 4.3% of 93 children 14,15 . Praveen‐Kumar et al primarily assessed radiological spectrum among 33 patients with SSPE; 27% had extrapyramidal involvement and 100% had myoclonus 16 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Movement disorders were the presenting feature in seven (14%) children. Two studies noted that SSPE contributed to movement disorders among 5.7% of 53 adults and 4.3% of 93 children 14,15 . Praveen‐Kumar et al primarily assessed radiological spectrum among 33 patients with SSPE; 27% had extrapyramidal involvement and 100% had myoclonus 16 .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies noted that SSPE contributed to movement disorders among 5.7% of 53 adults and 4.3% of 93 children. 14,15 Praveen-Kumar et al primarily assessed radiological spectrum among 33 patients with SSPE; 27% had extrapyramidal involvement and 100% had myoclonus. 16 Dash et al in an abstract reported that 12.2% of 106 patients (age range 7-17 years) with SSPE had movement disorders.…”
Section: Frequency Of Movement Disorders In Sspementioning
confidence: 99%